PENGARUH CARA BELAJAR, KECERDASAN EMOSIONAL DAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR KOGNITIF MATA PELAJARAN ADMINISTRASI UMUM PADA SISWA KELAS X SMK KRISTEN 1 SURAKATA - -, Steven Amos Samosir -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This research aims to know: (1) the effect of  learning strategy, emotional intelligence and family environment towards student achievement of general administration on student grade X of Vocational High School Kristen 1 of Surakarta, (2) the effect of learning strategy towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta, (3) the effect of  Emotional Intelligence towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta, (4) the effect of  family environment towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta.      The object of this research is student grade X in Vocational High School Kristen 1 Surakarta which is get general administration which amounting to 83 students. Questionnaires and documentation are used as data collection tools. Questionnaires are used to collect data of  learning strategy, Emotional Intelligence and family environment, while documentation is used to collect data on results student avhievement of general administration. Data analysis techniques used Regression test.     The results of this research are (1) there is a significant learning strategy, Emotional Intelligence and family environment towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta with the result of count Fcount>Ftable (87,381 > 2,720) (2) there is a significant effect the learning strategy towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta with the result of count ttest>ttable (2,853 >1,664) and significance 0,006 < 0,05 (3) there is a significance effect of Emotional Intelligence towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta with the result of count ttest>ttable (4,338 >1,664) and significance 0,000 < 0,05, (4) there is a significance effect of family environment towards student achievement of general administration on student grade X of Vocational High School Kristen 1 Surakarta with the result of count ttest>ttable (3,481 >1,664) and significance 0,001 < 0,05.